Clinical utility of extended red blood cell parameters in the diagnosis of latent iron deficiency and thalassaemia trait in Hospital Universiti Sains Malaysia - Sockalingam, Sivanesan (2023)
Introduction: Recognition of latent iron deficiency (LID) and thalassemia trait (TT) are challenging with the use of standard red blood cell (RBC) parameters. Accurate diagnosis is vital as the management of iron deficiency and haemoglobinopathy are different. The use of extended RBC parameters - reticulocyte haemoglobin equivalent (RET-He), percentage of microcytic RBC <60fL (MicroR), and percentage of hypochromic RBC <17pg (HYPO-He) may aid in the detection of LID and TT. The study aims to determine the diagnostic ability of these extended RBC parameters to distinguish LID and TT. Methodology: This was a prospective, case-control study conducted in Hospital USM from August 2021 to June 2022. 162 out of 212 blood donors who fulfilled the inclusion criteria were classified into the control group, LID group and TT group based on RBC parameters, serum ferritin and thalassaemia status. Between-group comparisons, receiver operating characteristic (ROC) curve analysis and comparison of area under the curve (AUC) for the RBC parameters were determined. The optimal cut-off was determined using the best Youden index. Result: There were 17 (10.5%) subjects with LID, 26 (16.0%) subjects with TT and 119 (73.5%) subjects in the control group. Standard RBC parameters were within the reference interval for all groups except for RBC (in females), MCV and MCH in the TT group. In LID and TT, RET-He and MicroR were lower and higher than the reference interval respectively, while HYPO-He was within the reference interval in all the groups. Taking into consideration the reference interval, RET-He was the best parameter to distinguish LID (AUC 0.723, 95% CI 0.608-0.839; 76.47% sensitivity and 73.95% specificity at 30.1pg cut-off) and TT (AUC 0.832, 95% CI 0.749-0.914; 84.62% sensitivity and 73.11% specificity at 30.2pg cut-off) from control. MicroR was the best parameter to distinguish TT from LID (AUC 0.742, 95% CI 0.591-0.893; 65.38% sensitivity and 76.47% specificity at 6.5% cut-off). Although the AUC of RET-He and MicroR were not significantly different in all the case comparisons, only MicroR was significantly higher in TT (median 9.1%, IQR 17.5) than LID (median 4.0%, IQR 6.1). Conclusion: Among the extended RBC parameters, RET-He was the best parameter for the detection of LID and TT, while MicroR performed well in differentiating TT from LID. These accessible parameters through modern automated haematology analyzers are low cost, with high throughput and rapid turn-around time can optimize the management of iron deficiency and thalassemia screening in the population.